Age at peak height velocity in Polish adolescents: Effect of socioeconomic factors - Gomula, Aleksandra; Nowak-Szczepanska, Natalia; Králík, Miroslav; Malina, Robert M; Zaręba, Monika; Koziel, Slawomir (American journal of human biology, 2024)
Age at peak height velocity (APHV) is an indicator of maturity timing which is applicable to both sexes, and which is influenced by environmental factors. The objective of this study was to assess variation in APHV associated with several indicators of socioeconomic status (SES) in a longitudinal sample of Polish adolescents. The sample included 739 boys born in 1983 and followed annually from 12 to 16 years, and 597 girls born in 1985 and followed annually from 9 to 13 years. The height records were fitted with the SITAR model to estimate APHV. SES was estimated using principal component analysis of indicators of familial status based on parental education, family size, living conditions and household possessions. Statistical analyses included analysis of variance (one-way for general SES and three-way for parental education and family size) and Tukey post-hoc tests for unequal samples. General SES (p <.001) and family size (p < .05) significantly influenced APHV among boys, while only maternal education (p < .05) significantly influenced APHV among girls. Among youth from families of higher SES, as defined by the respective indicators, APHV was attained significantly earlier, on average, than in peers from families of lower SES. Overall, the results showed a sex-dependent effect of SES on APHV, and highlighted the influence of favorable socioeconomic conditions for optimal growth and maturation during adolescence.
Keywords: Socioeconomic Factors; společenská třída; vývoj mladistvých; Male; longitudinální studie; Social Class; Adolescent; sexuální faktory; Poland; Child; dítě; socioekonomické faktory; Body Height; mužské pohlaví; tělesná výška; mladiství; lidé; ženské pohlaví; Humans; Sex Factors; Longitudinal Studies; Female; Polsko; Adolescent Development